"Executive Class" in Public Service: A Phenomenon in The Implementation of The New Public Management (NPM) Paradigm in Indonesia - Fadoli, M. Irsyad; Putra, Purwanto; Fadhlillah, Nibras; Faedlulloh, Dodi (Iapa Proceedings Conference, 2024)
This study aims to examine how the executive class in public services reinforces the implementation of New Public Management (NPM) in Indonesia and its impact on justice in good governance. Using a literature review method, the study collects and analyzes secondary sources such as books, articles, and policy documents related to executive class public services and NPM. The findings highlight the negative effects of the executive class system on both accessibility and fairness within public services. It shows that Indonesia's adoption of executive class services is a direct result of NPM's focus on efficiency and outcomes. However, this approach often leads to inequity, reduced accessibility, and misalignment with the core principles of public service. As a result, reforms are necessary to address these challenges by placing greater emphasis on justice, transparency, and inclusivity in public services. The study recommends abolishing or restricting the executive class system, improving the transparency and accountability of service costs, and implementing the New Public Service (NPS) and New Public Governance (NPG) frameworks to develop a fairer and more responsive public service system that better meets the needs of the public.